PELAYANAN PEMERIKSAAN SPERMA RUTIN BAGI PASANGAN YANG BELUM DIKARUNIAI KETURUNAN - Renny Sulelino; Leddy N. Rumansara (LPPM Uncen, 2022)
The Infertility in humans is influenced by several factors, one of which is the quality of the spermatozoa of the male partner. Facts in the field there are still many couples who have not had children during their marriage for at least a year under normal circumstances/not far apart. This service uses a service approach to test the analysis of spermatozoa in a consecutive way in the laboratory of the Faculty of Medicine, Cenderawasih University, Jayapura. The results of the examination showed that from 9 people, 2 people had abnormalities consisting of 1 male asthenozoospermia at the age of 36 years, while one with teratozoospermia at the age of 45 years. Data on two people with spermatozoa status disorder are both active smokers and spend at least 3 packs of cigarettes a day with different brands. The work of both people is private and the other is a Civil Servant.Keywords: Infertility; spermatozoa; laboratory; quality; smoker